2012
DOI: 10.1179/1743294411y.0000000072
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, nanomechanical and antibacterial properties of magnetron sputtered nanocomposite thin films of CrN/Cu

Abstract: Synthesis of nanocomposite thin films of CrN/Cu on (100) Si and titanium modified stainless steel (D-9 alloy) substrates by pulsed magnetron sputtering from a composite target of Cr-Cu using sputtering gas mixture of argon and nitrogen is investigated. X-ray diffraction analysis of the films deposited at 773 K and 10 sccm of nitrogen flowrate indicated that the films are nanocrystalline and biphasic (fcc CrN and fcc Cu). The films showed a peak hardness of y15 GPa and a Young's modulus of y200 GPa for those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Ag or Cu), as a solid lubrication phase, embedded in a hard wear-resistant matrix, such as a transition metal nitride [2][3][4][6][7][8][9], carbide [10,13] or oxide [14][15][16], and mixtures of these ceramics (in ternary/quaternary/nanocomposite coating systems), have all been extensively studied, with the promise of improved tribological performance during transient and/or cyclic temperature changes [17][18][19]. In particular, coatings based on Cr-Ag-N [7,8,[17][18][19][20][21] and Cr-Cu-N [6,22,23] (as two typical coating systems), have been studied. For coatings in the Cr-Ag-N system, it is revealed that Ag precipitates often tend to exhibit a lamellar shape (height/width: ~ 1/2 to 1/3), with a uniform, but isolated distribution in the ceramic nitride matrix of the deposited coating [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Ag or Cu), as a solid lubrication phase, embedded in a hard wear-resistant matrix, such as a transition metal nitride [2][3][4][6][7][8][9], carbide [10,13] or oxide [14][15][16], and mixtures of these ceramics (in ternary/quaternary/nanocomposite coating systems), have all been extensively studied, with the promise of improved tribological performance during transient and/or cyclic temperature changes [17][18][19]. In particular, coatings based on Cr-Ag-N [7,8,[17][18][19][20][21] and Cr-Cu-N [6,22,23] (as two typical coating systems), have been studied. For coatings in the Cr-Ag-N system, it is revealed that Ag precipitates often tend to exhibit a lamellar shape (height/width: ~ 1/2 to 1/3), with a uniform, but isolated distribution in the ceramic nitride matrix of the deposited coating [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the heavy metal ions such as Cu 2+ can kill bacteria by destroying their proteins [50]. Kuppusami et al [51] demonstrated that CrN/Cu coatings containing 15.1 wt% copper had a durable antibacterial effect, which copper ions were responsible for destroying the cell walls of the bacteria and inhibiting their growth. Hadidi et al [52] reported HA-Cu nanocomposite coatings produced by the electrophoretic deposition method on the Ti6Al4V substrates and suggested that the coating containing 5 wt% copper expressed both a powerful anti-bacterial and anti-infection activities and good cytocompatibility.…”
Section: Microbiological Studiesmentioning
confidence: 99%
“…As a coating, CrN exhibits stronger wear-resistance properties than TiN because its friction coefficient is slightly lower than that of TiN [ 5 , 6 ]. CrN films have been widely used in the industry owing to their high hardness and toughness [ 7 , 8 , 9 ], good oxidation [ 10 ] and corrosion [ 11 ] resistance, prominent tribological properties [ 12 , 13 ], and excellent adhesion to substrates [ 14 ]. However, most of the transition metal nitride coatings have a high friction coefficient (0.6–0.8) and their tribological effectiveness [ 15 ] is insufficient under severe tribological conditions such as high temperature, high-speed operation and high-applied pressure.…”
Section: Introductionmentioning
confidence: 99%